1999
DOI: 10.1606/1044-3894.1780
|View full text |Cite
|
Sign up to set email alerts
|

The Home Environment and Delinquency: A Study of African American Adolescents

Abstract: This study sought to determine the relationship between an adolescent's home environment and his/her involvement in conduct disorder. The study was based on a sample of 556 African American adolescents (85% males) aged thirteen to seventeen and enrolled in violence prevention programs at historically black colleges and Universities (HBCUs) located in eight states and the District of Columbia. The HBCUs in this study have student bodies that are predominantly African American. Data were collected using a conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Gorman-Smith, Tolan, Zelli, and Huesmann (1996) found that both family characteristics and parenting practices contribute to risk for serious delinquent behavior. These risk factors for children may be amplified by the rise in divorce rates (Gordon, Jurkovic, & Arbuthnot, 1998), economic hardship, and poverty (Kumpfer, 1999;Thornberry et al, 1999), especially for families of color (McLoyd, 1990;Rodney, Tachia, & Rodney, 1999).…”
Section: Familial Influences On Delinquent and Antisocial Behaviormentioning
confidence: 99%
“…Gorman-Smith, Tolan, Zelli, and Huesmann (1996) found that both family characteristics and parenting practices contribute to risk for serious delinquent behavior. These risk factors for children may be amplified by the rise in divorce rates (Gordon, Jurkovic, & Arbuthnot, 1998), economic hardship, and poverty (Kumpfer, 1999;Thornberry et al, 1999), especially for families of color (McLoyd, 1990;Rodney, Tachia, & Rodney, 1999).…”
Section: Familial Influences On Delinquent and Antisocial Behaviormentioning
confidence: 99%
“…Studies that examined delinquent behavior among Black adolescents ( Pittman & Chase-Lansdale, 2001 ;Rodney, Tachia, & Rodney, 1999 ) have focused mostly on crime and criminal behavior among this population. These studies suggest that the cause of high involvement of Black youth in the justice system is due to their overinvolvement in criminal activity and delinquent behavior, rather than to parental-or family-level factors, adolescent's perceptions of their attachment relationship with their parent or primary caretaker, or future orientation.…”
Section: Research On Delinquency and Black Adolescentsmentioning
confidence: 99%
“…These factors are associated with the individual, community, family, peers, and school (Stinson, 2002;Rodney et al, 1999a;Hawkins, 1995;Howell, 1995;. Although all categories are important for understanding the context of a given act of youth violence, only those that are associated with schools are discussed in this chapter.…”
Section: Factors Associated With School Violence: How They May Be Redmentioning
confidence: 99%